الموضوعية في التدوين الشرعي عند الإمام السالمي : دراسة تحليلية - مقبمي، أسعد حمود سبيت
This study aims to demonstrate the objectivity concept and its benchmarks in Islamic writings to reveal the concept continued realisation and applicability in the transcription of Imam Al Salmi’s books based on solid evidence. This study adopts two approaches to address the lack of definitive benchmarks to determine the objectivity principle in Islamic writing – the first is purely theoretical meant to come up with a governing term of reference for the objectivity in writing and transcription, whilst the second one is practical, which is meant to determine the materialisation of such terms of reference in Imam Al Salmi’s writings. This study uses inductive, historical, deductive and critical methods in addition to the content analysis tool. It includes five chapters, chapter one-an introduction, chapter two - definition of the keywords; chapter three- the evolution of the objectivity concept and its connection with academic research; chapter four-objectivity benchmarks in writing, documentation and reasons for being missed; chapter five- identification of objectivity benchmarks in Imam Al-Salmi’s writing. The most important conclusion is the identification of fourteen benchmarks for objectivity in writing. All are summed up in five generic benchmarks, including adherence to evidence, appreciation of difference and divergence in opinion, being fair enough to the different opinions, thorough understanding before making any hasty judgment and documentation. This study found that the objectivity benchmarks were sufficiently observed and maintained in Imam Al Salmi’s books. However, any variation in these benchmarks could be exclusively contextual. The two benchmarks: documentation and evidence, feature most prominently in Imam Al-Salmi’s discourse with themes that could be non-objective in the reader’s opinion. These should be understood within their respective historical context or following the conventional methods of writing used by early scholars. The study recommended that objectivity benchmarks be improved and circulated to serve as a reference for the objectivity appraisal in Islamic writing, and documentation for precise and meticulous identification of the concept.